Meta-Analysis: Effects of Workload and Work Environment on Work Satisfaction in Health Personnel - Wulansari, Galuh; Murti, Bhisma; Tamtomo, Didik (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2023)
Background: Job satisfaction is one of the important points to motivate and improve work efficiency, high job satisfaction can improve the performance of health workers and patient satisfaction. However, low job satisfaction results in fatigue and a tendency to increase the turnover of health workers which will exacerbate the condition of health facilities. The research objective was to analyze the effect of workload and work environment on job satisfaction in health workers. Subjects and Method: This study is a meta-analysis with PICO. Population: health workers. Intervention: high workload and safe work environment. Comparison: low workload and unsafe work environment. Outcome: job satisfaction. The articles used in this study were obtained from three databases namely Google Scholar, Science Direct and Pubmed. The keywords used to search for articles are “Workload” OR “Job Overload” AND “Safe Work Environment” AND “Job Satisfaction” AND “Health Workers” AND “Multivariate”. The articles used were full text in English from 2012 to 2022. Articles were selected using the PRISMA flowchart and analyzed using the RevMan 5.3 application. Results: A total of 17 cross-sectional study articles from Ethiopia, Switzerland, Israel, Belgium, China, Canada and Denmark. Based on the analysis, health workers with high workloads reduced job satisfaction 0.47 times compared to health workers with low workloads and this was statistically significant (aOR=0.47; 95% CI=0.24 to 0.92; p=0.030). Health workers with a safe work environment increased job satisfaction 2.75 times compared to health workers with an unsafe work environment and this was statistically significant (aOR=2.75; 95% CI=1.59 to 4.78; p=0.003). Conclusion: High workload reduces job satisfaction in health personnel and a safe work environment increases job satisfaction in health personnel. Keywords: workload, work environment, job satisfaction Correspondence: Galuh Wulansari. Masters Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta 57126, Jawa Tengah, Indonesia. Email: Galuhwulan61@gmail.com. Mobile: 085601548168.